A local chemical environment effect in site-specific Auger spectra of ethyl trifluoroacetate - Iwayama, Hiroshi; Sisourat, N.; Lablanquie, P.; Penent, F.; Palaudoux, J.; Andric, L.; Eland, J. H. D.; Bučar, K.; Žitnik, M.; Velkov, Yasen; Hikosaka, Y.; Nakano, M.; et al. (The journal of chemical physics, 2013)
We have investigated a local chemical environment effect on Auger spectra of ethyl trifluoroacetate (C4H5F3O2), using multi-electron coincidence spectroscopy and high-resolution electron spectroscopy. Site-specific KVV Auger spectra for each carbon atom, and for the fluorine and oxygen atoms are presented. The extent of hole localization in the final dicationic states was investigated with the help of theoretical calculations based on a two-hole population analysis. The Auger spectra have been simulated using a statistical approach. It is found that all Auger decays populate mainly localized dicationic states, with the two holes located either on the same fluorine atom or on adjacent fluorine atoms. While the decay of the F 1s hole populates exclusively the former states, the latter class of states is also populated by the decay of the C and O 1s holes.
Gesehen am 18.03.2021